A Study of Brand Narrative Storytelling Executions - Lamuang, Ackapol; Srikanlayanabuth, Araya (Journal of Fine and Applied Arts Khon Kaen University, 2024)
Businesses or brands with clear brand storytelling goals, along with the appropriate choice of brand narrative storytelling executions, can effectively communicate with consumers. However, most businesses or brands lack suitable executions for storytelling in designing various public relations media. This article aims to (1) study narrative structure in data story (2) study narrative executions in journal, advertising, and movies and (2) to identify data storytelling executions for brand communication. The author used relevant literary studies as the primary tool for analysis concepts related to the storytelling techniques in journals, news, advertisements, and movies, together with in-depth interviews in a semi-structured format with 10 experts for extensive consideration and validation. To address this gap, the study identifies six narrative storytelling executions: (1) Journey (2) Slice (3) Amazement (4) Single Message (5) Argument, and (6) Conviction. These findings may help designers and brand responsible persons to improve data-visualization and media for future communication by incorporating effective brand narrative storytelling executions.